2015
DOI: 10.1021/jp5127909
|View full text |Cite
|
Sign up to set email alerts
|

Phase- and Size-Dependent Optical and Magnetic Properties of CoO Nanoparticles

Abstract: A simple pyrolysis method has been developed to synthesize microstructure-controlled CoO nanoparticles from cobalt acetylacetonate in oleylamine at or above 200 °C. XRD, SEM, and HRTEM analyses indicate that the cubic and hexagonal CoO nanoparticles with different morphologies, viz. spherical, quasi-cubic, and pyramidal, could be obtained via varying the precursor concentration, and the average size of hexagonal CoO nanoparticles increases with increasing reaction time or reaction temperature. XPS, TG-DTA, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(42 citation statements)
references
References 71 publications
3
38
0
1
Order By: Relevance
“…The values for a and c are in line with previously reported lattice parameters of wurtzite‐CoO (JCPDS no. 80‐0075) . On the other hand, the sample obtained in a large batch shows a mixture of wurtzite‐CoO ( a = 3.2526(1) Å, c = 5.1976(1) Å; < D > W = 32.0(5) nm) and cubic zinc blende‐CoO structures (space group F4¯3m; a = 4.5533(1) Å, < D > ZB = 13.0(5) nm – Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values for a and c are in line with previously reported lattice parameters of wurtzite‐CoO (JCPDS no. 80‐0075) . On the other hand, the sample obtained in a large batch shows a mixture of wurtzite‐CoO ( a = 3.2526(1) Å, c = 5.1976(1) Å; < D > W = 32.0(5) nm) and cubic zinc blende‐CoO structures (space group F4¯3m; a = 4.5533(1) Å, < D > ZB = 13.0(5) nm – Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been shown that surface effects and bulk defects (e.g., vacancies) may lead to uncompensated spins resulting in a ferromagnetic‐like response . Experimentally, opposing magnetic behaviors have been reported for wurtzite‐CoO, ranging from antiferromagnetic or ferromagnetic‐like to paramagnetic . This probably stems from the strong magnetic signal of the uncompensated spins which smears out any intrinsic magnetic properties of wurtzite‐CoO.…”
Section: Introductionmentioning
confidence: 99%
“…Back-scattering Raman spectroscopy was used to study phonon anomalies and spin-phonon couplings. [48]. The powders were mixed in an agate mortar with alcohol as a medium for more than 24 h. The dried mixtures were calcined at 800°C (3 h) for all compounds and then sintered at 830°C (10 h) for BFO, and 850°C (3 h) for BFO5Co and BFO15Co.…”
Section: Introductionmentioning
confidence: 99%
“…Peaks located at 297.95, 353.35 and 640.31 cm −1 for x=0.2 are red shifted compared to those of the un-doped material, due to the alloying of CoO with the MnO host structure. The small peaks located at 172.04 and 461.42 cm −1 were assigned to CoO [44] in the x=0.2 sample. Highresolution TEM analysis (figures 1(c), (d); and S1, supporting information is available at stacks.iop.org/NANO/28/155403/ mmedia) confirms the nucleation and growth of MnO and Mn 0.8 Co 0.2 O nanoparticles onto the outer walls of the MWCNTs.…”
Section: Resultsmentioning
confidence: 95%